Determinants of Non-Performing Financing Risk in Islamic Commercial Banks in Indonesia - Yusuf, Andi Muhammad; Hamid, Abdul; Nafis, M. Cholil (Jurnal Minds: Manajemen Ide dan Inspirasi, 2024)
This research comprehensively investigates the causes of NPF risk factors and proposes control strategies in Indonesian Islamic Banking. This model constructs a research model by Employing Generalized Least Squares, Path Analysis, Analytical Hierarchy Process (AHP), and Interpretative Structural Modelling (ISM). The data is pooled from 12 Indonesian Islamic banks from 2012 to 2020. These exhaustive analyses reveal an intricate building of unresolved debts. Some key findings in the financial ratios support the positive impact of good corporate governance (GCG) and Islamic corporate social responsibility (ICSR) on NPF. In contrast, asset utilization (AUR) negatively affects NPF. Furthermore, profitability and operation costs increase NPF. Some indirect paths are also realized. This research proposes a more holistic approach to forming NPFs in Islamic banking, critical for managerial decision-making in drafting their budget structures.